Cognitive testing in older primary care patients: A cluster‐randomized trial. Issue 3 (21st July 2015) - Fowler, Nicole R.; Morrow, Lisa; Chiappetta, Laurel; Snitz, Beth; Huber, Kimberly; Rodriguez, Eric; Saxton, Judith
Abstract: Introduction: This study investigated whether neuropsychological testing in primary care (PC) offices altered physician‐initiated interventions related to cognitive impairment (CI) or slowed the rate of CI progression. Methods: This 24‐month, cluster‐randomized study included 11 community‐based PC practices randomized to either treatment as usual (5 practices) or cognitive report (CR; 6 practices) arms. From 2005 to 2008, 533 patients aged ≥65 years and without a diagnosis of CI were recruited; 423 were retested 24 months after baseline. Results: CR physicians were significantly more likely to order cognitive‐related interventions ( P  = .02), document discussions about cognition ( P  = .003), and order blood tests to rule out reversible CI ( P  = .002). At follow‐up, significantly more CR patients had a medication for cognition listed in their chart ( P  = .02). There was no difference in the rate of cognitive decline between the groups. Discussion: Providing cognitive information to physicians resulted in higher rates of physician‐initiated interventions for patients with CI.